Análisis de las consecuencias socioeconómicas en el municipio de Pamplona producto de la crisis binacional con Venezuela. - José Luis Jaimes Quinchoa; Gendler Alexander Jaimes Gauta; Nathalie Hernández Pérez (Mundo Fesc)
This study aims to analyze the impact of the binational crisis between Colombia and Venezuela on the municipality of Pamplona. It is important to note that this research employed an inductive methodology, using the limited Delphi method, which surveyed experts in different fields of knowledge. A probabilistic econometric model was also estimated to compare the results obtained in the municipality of Pamplona with those in the department of Norte de Santander. The estimates were based on data provided by the National Administrative Department of Statistics (DANE), specifically the Large Integrated Household Survey (GEIH). Among the main findings , the migration crisis affected the municipality's commercial and industrial sectors and exacerbated social problems such as security and domestic abuse. Likewise, a comparison of the results for the municipality of Pamplona with those for the department showed that Venezuelan migration had an impact on the labor market, as it increased competition for labor in different sectors of the economy.